2019
DOI: 10.1016/j.ultsonch.2019.02.010
|View full text |Cite
|
Sign up to set email alerts
|

A simple method to analyze the super-harmonic and ultra-harmonic behavior of the acoustically excited bubble oscillator

Abstract: Acoustically excited bubbles are involved in a wide range of phenomena and applications ranging from oceanography to sonoluminescence; they have applications in chemistry, medical imaging, and therapeutic ultrasound. The complexity of bubble dynamics and the limited understanding of their behavior restricts the exploration of their full potential. The bubble oscillator is a highly nonlinear system, which makes it difficult to generate a comprehensive understanding of its oscillatory behavior. One method used t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 57 publications
(100 reference statements)
1
38
0
Order By: Relevance
“…where D is the thermal diffusivity of the gas which can be calculated using a = L cpρg where L is the gas thermal conductivity and c p is specific heat capacity at constant pressure and ρ g is the gas density. Predictions of the ODE thermal model have been shown to be in good agreement with predictions of the models that incorporate the thermal effects using the PDEs [45] that incorporate the temperature gradients within the bubble. To calculate the radial oscillations of the uncoated bubble while including the thermal effects, Eqs.…”
Section: Ode Thermal Modelmentioning
confidence: 64%
“…where D is the thermal diffusivity of the gas which can be calculated using a = L cpρg where L is the gas thermal conductivity and c p is specific heat capacity at constant pressure and ρ g is the gas density. Predictions of the ODE thermal model have been shown to be in good agreement with predictions of the models that incorporate the thermal effects using the PDEs [45] that incorporate the temperature gradients within the bubble. To calculate the radial oscillations of the uncoated bubble while including the thermal effects, Eqs.…”
Section: Ode Thermal Modelmentioning
confidence: 64%
“…Dissipation effects of Td become weaker for smaller bubbles and when the gas core is C3F8. We showed that scattering to damping ratio (STDR) is pressure dependent; STDR grows with pressure at pressure dependent resonance frequencies (P Df r [24]) and at super harmonic resonances of the system (SuHf r [23]). STDR is generally higher at f > f r .…”
Section: Discussionmentioning
confidence: 99%
“…Dynamics of the acoustically excited bubbles are nonlinear and chaotic. These dynamics have been the subject of numerous experimental [1,15,[17][18][19][20] and numerical [21][22][23][24][25][26][27][28][29][30] studies . Achieving the full potential of bubbles in applications and understanding their role in the associated phenomena not only requires a detailed knowledge over their complex behavior but also on the effect of bubble oscillations on the propagation of acoustic waves.…”
Section: Introductionmentioning
confidence: 99%
“…It has demonstrated that the qualitative and quantitative changes of the nonlinear dynamics could be investigated effectively over a wide range of control parameters [43] , [45] , [46] , [47] , [48] , [49] . However, the conventional bifurcation analysis may be misleading and cannot reliably identify features that are responsible for the identification of super-harmonic and ultra-harmonic oscillations [43] , [50] , [51] , [52] , [53] . Thus, a more comprehensive bifurcation analysis method was used herein to investigate the nonlinear dynamics of the coupled two-bubble system for a wide range of control parameters as described previously [43] , [50] , [51] , [52] , [53] .…”
Section: Theory and Methodsmentioning
confidence: 99%